Sosiologi Komunikasi: teori, Paradigma dan Diskursus Teknologi Komunikasi di Masyarakat - Burhan Bungin (Kencana, 2006)
Sosiologi Komunikasi: teori, Paradigma dan Diskursus Teknologi Komunikasi di Masyarakat